Administrasi Islam Memandang Kebijakan Negara Dalam Melindungi Hak Milik Pribadi Dan Umum - Cipta Lukmanul Hakim; Aip Zaenal Muttaqin (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
The purpose of this study is to determine the state's protection of ownership both individual ownership and general ownership. The method used in this research is to use literature studies. After conducting a review of various information found that in Islam economic arrangements are regulated in the Qur'an and the Sunnah of the Prophet Muhammad. Then the Islamic economy does not run alone as understanding or other conventional economic concepts. the focus of Islamic economic studies or Islamic economics one of which is regarding the ownership of property. In Islam ownership is very flexible unlike capitalism which emphasizes freedom or socialism which forbids individual ownership. In the level of individual ownership, Islam really values and even protects it. More than that ownership in Islam can be more beneficial for others so that ownership does not depend on just one person. Instruments in the ownership of individual Islam accommodate through various things such as: the management of orphans' property, the distribution of inheritance, the obligation to pay zakat.